Development and Validation of the Holistic Cognition Scale - Lux, Andrei Alexander; Grover, Steven Lee; Teo, Stephen Tai Theng (Frontiers in Psychology, 2021)
This paper introduces a new scale to measure cognitive cultural differences, drawing on the theory of analytic versus holistic thought. Examining culture from a cognitive perspective is a challenge to traditional values-based approaches. Existing measures based on this framework are methodologically problematic and warrant renewal. This paper presents development and validation studies for a new instrument that measures analytic versus holistic cognitive tendencies at the individual level. The scale assesses four previously established dimensions: attention, causality, contradiction, and change. The present work follows well-established scale development protocols and the results show that the 16-item Holistic Cognition Scale (HCS) is a valid and reliable measure of analytic versus holistic thought. Three new studies with four unique samples (N = 41; 272; 454; and 454) provide evidence to support the content validity, reliability, and factor structure of the new instrument, as well as its convergent, discriminant, and concurrent validity against comparable constructs. Convergent validity is established against measures of compromise, intuition, complexity, and collectivism; predictive validity is established against Hofstede’s (1980) five cultural value dimensions; and discriminant validity is established using the average variance extracted from a confirmatory factor analysis. The new HCS is an improvement over previous attempts with a balanced number of forward- and reverse-scored items, superior reliability, less redundancy, and stronger factor loadings.